Sebaceous adenoma of the parotid gland encasing the facial nerve: Case report and review of the literature - Bhavik Singh; Kelly R. Magliocca; David Chou; Jennifer H. Gross; Jennifer L. Becker; Nicole C. Schmitt (Oral Oncology Reports)
Background: Sebaceous adenoma of the salivary glands are uncommon benign neoplasms, comprising about 0.1 % of salivary tumors. These tumors can be difficult to recognize with heterogeneous appearance on imaging. Case report: A 67-year-old man presented with a painless, progressively growing left parotid mass. Imaging showed a heterogenous, partially cystic mass in the superficial and deep lobes of the parotid with some areas of adipose density. Intraoperatively, a mass with sebaceous differentiation was found to be encasing the main trunk and pes anserinus of the facial nerve, requiring nerve sacrifice for en bloc resection. Final pathology revealed a sebaceous adenoma with intense xanthomatous reaction compressing the facial nerve. Conclusion: Although benign and associated with little risk of recurrence, sebaceous adenomas may be difficult to recognize on preoperative workup and may be locally aggressive. Complete surgical resection is the mainstay of therapy, but rehabilitation may be required in the event of facial nerve involvement.